Evaluation of Competency Achievement Levels of Lecturers at State Christian Religious Universities - Siahaya, Agusthina; Tuhuteru, Ajuan; Panggabean, Erika Christine; Ambarita, Jenri (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
This study aims to evaluate lecturer competencies at State Christian Religious Universities (PTKKN) in Indonesia, focusing on pedagogic, personality, social, and professional dimensions. Lecturers from seven state Christian higher education institutions (HEI)—Ambon, Manado, Tarutung, Toraja, Palangkaraya, Kupang, and Sentani—were sampled, with 21 lecturers selected from each institution for a total of 147 participants. Mix-method research was employed, incorporating a questionnaire based on Perdirjen Number 2626 of 2023 for the quantitative analysis, which involved descriptive statistics to summarize the data. Qualitative data were gathered through online in-depth interviews with five lecturers from each institution, selected based on survey responses to ensure data saturation. Thematic analysis and data triangulation were used to provide a richer understanding of the quantitative findings. The study revealed that most lecturers are at Levels 1 and 2, demonstrating a basic understanding and application of pedagogical competencies but needing further development in evaluation, reflection, collaboration, and mentoring. Lecturers at Level 3 showed proficiency in evaluation and improvement, while Levels 4 and 5 exhibited advanced collaboration and expert mentoring skills. Challenges identified include additional workload and administrative responsibilities at lower levels and difficulties in engaging less experienced colleagues at higher levels. This study recommends enhancing development programs to improve foundational knowledge at Levels 1 and 2, reinforcing collaboration and mentoring at Levels 3 and 4, and addressing workload issues to support professional growth. Continuous professional development is crucial for improving educational quality and advancing lecturer competencies at Christian HEI